Pengaruh Standar Akuntansi Pemerintah, Kompetensi Sumber Daya Manusia, dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah - Roni Setiawan; Raihan Aditya Perkasa; Zacky Maulana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this research is to determine the impact of the implementation of Government Accounting Standards (SAP), Human Resource Capability (HRM), and Internal Control System (ICS) on the quality of government financial reporting. The research method involves a systematic literature review. The strategy for selecting journal articles related to the quality of government financial reporting is influenced by factors such as government accounting standards, internal government control systems, and human resource capabilities. Financial reports serve as a form of accountability for the management of national/regional finances within a specific time frame. The focus or objective of financial reports is to provide quality information that is useful to its users.